PENGARUH METODE SHOW AND TELL BERBANTUAN MEDIA KANTONG PERKALIAN TERHADAP HASIL BELAJAR KONSEP PERKALIAN - Anggun Swi Purba (Universitas Negeri Medan, 2026)
Third-grade students are generally expected to understand the basic concept of multiplication as repeated addition. However, conditions in the field indicate that many students still have difficulty understanding this concept properly. Therefore, this study applied the Show and Tell method, which is student-centered, assisted by a concrete learning medium called the Multiplication Pocket to improve students’ learning outcomes. This study used a quasi-experimental design with a nonequivalent control group design. The research sample consisted of 50 students, including 24 students in the experimental class and 26 students in the control class. Data were collected through pretest and posttest instruments. The results showed that the average score of the experimental class increased from 11.17 to 15.04, while the control class increased from 11.88 to 12.69. The homogeneity test showed a significance value of 0.714 > 0.05, indicating that the data were homogeneous. Furthermore, the hypothesis test using an independent sample t-test obtained a significance value (2-tailed) of 0.043 ≤ 0.05, meaning that H₀ was rejected and Hₐ was accepted. The N-Gain score of the experimental class was 0.44 (moderate category), while the control class obtained 0.10 (low category). Therefore, the Show and Tell method assisted by the Multiplication Pocket medium significantly affected third-grade students’ learning outcomes in multiplication concepts at SDN 104202 Bandar Setia.